Coaching and Mentoring Practices in School Context: Basis for Enhanced Coaching and Mentoring Program - Culajara, Carla Jobelle J.; Culajara, Juan Paolo Martin (ASEAN Journal of Education, 2024)
Coaching and mentoring are essential components in both personal and professional growth. It provides guidance, support, and knowledge to attain the teachers’ full potential as well as to accomplish and attain the curriculum goals. The study used a qualitative research design employing phenomenological approach in a secondary public school in the Philippines using Focus Group Discussion (FGD) to acquire an in-depth understanding on the coaching and mentoring practices. Participation in FGDs was by eight (8) master teachers also known as “Highly Proficient Teachers”. The FGDs aimed to explore and analyze the positive effects of coaching and mentoring, assisting teachers’ in enhancing instructional competencies and to formulate inputs toward coaching and mentoring. An interview guide was used in the study to acquire an in-depth understanding on the coaching and mentoring practices. Based on the responses, themes emerged: Knowledge Transfer, Strengthening Teachers Capabilities, Positive Organizational Culture, Individual Support, Feedback and Reflection, Peer Learning. Through these themes, the researcher aims to provide inputs to policy formulation in the school-based coaching and mentoring practices. Coaching and mentoring allowed the growth and enhancement of teacher instructional competencies. Thus, coaching and mentoring emphasize the value of strengthening and producing a positive organizational culture as well as the development of skills and competencies.